2022
DOI: 10.1111/desc.13321
|View full text |Cite
|
Sign up to set email alerts
|

Hearing water temperature: Characterizing the development of nuanced perception of sound sources

Abstract: The data that support the findings of this study are openly available in an OSF repository https://osf.io/brp2a/?view_only=7f49783ebbf646b29af32ca645246f57.We thank Viola Stormer and Tim Brady for conversations inspiring this line of work, as well as

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 116 publications
(175 reference statements)
0
4
0
Order By: Relevance
“…Early research on cue integration found that basic perception involves rapidly incorporating information from distinct sensory inputs (Ernst & Banks, 2002;Körding et al, 2007). In fact, people use multiple modalities to draw complex inferences about the structure of the environment and agents' behavior within it (Agrawal & Schachner, 2023;Gerstenberg et al, 2021;Schachner & Kim, 2018;Siegel et al, 2021). However, young children struggle with abstract multimodal inferences (Agrawal & Schachner, 2023;Gori et al, 2008;Outa et al, 2022) and models of adults have been limited to reasoning about physical events (e.g., Gerstenberg et al, 2021).…”
Section: Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Early research on cue integration found that basic perception involves rapidly incorporating information from distinct sensory inputs (Ernst & Banks, 2002;Körding et al, 2007). In fact, people use multiple modalities to draw complex inferences about the structure of the environment and agents' behavior within it (Agrawal & Schachner, 2023;Gerstenberg et al, 2021;Schachner & Kim, 2018;Siegel et al, 2021). However, young children struggle with abstract multimodal inferences (Agrawal & Schachner, 2023;Gori et al, 2008;Outa et al, 2022) and models of adults have been limited to reasoning about physical events (e.g., Gerstenberg et al, 2021).…”
Section: Evidencementioning
confidence: 99%
“…In fact, people use multiple modalities to draw complex inferences about the structure of the environment and agents' behavior within it (Agrawal & Schachner, 2023;Gerstenberg et al, 2021;Schachner & Kim, 2018;Siegel et al, 2021). However, young children struggle with abstract multimodal inferences (Agrawal & Schachner, 2023;Gori et al, 2008;Outa et al, 2022) and models of adults have been limited to reasoning about physical events (e.g., Gerstenberg et al, 2021). Causal event reconstruction with multimodal evidence in situations involving agents has yet to be studied.…”
Section: Evidencementioning
confidence: 99%
“…Following this line of thought, one might consider whether making sounds of drinks being poured extra-cold might make them appear more refreshing, and hence more thirst-quenching (see also [ 86 ]). The research shows how sounds can be made to sound colder than cold—extra-chilled, in other words [ 92 , 93 , 94 ]. A drink that is seen being poured in an advert can be made to sound cooler, and hence presumably more thirst-quenching, simply by caricaturing actual pouring sounds to make a drink sound colder than cold (e.g., see ‘The sound of temperature’ for sonic examples: [ 95 ]).…”
Section: Temperature and Refreshmentmentioning
confidence: 99%
“…Children may perceptually learn the cross-modal correspondences (Chow et al, 2016;Nava et al, 2016). Starting from 7 years of age, children can accurately discriminate cold from hot water based on nothing more than sonic cues, while younger children do not show this ability (Agrawal & Schachner, 2022). Furthermore, auditory cues also allow for the differentiation of drinks having differing levels of carbonation.…”
Section: Introductionmentioning
confidence: 99%